The Role of User Privacy Concerns in Shaping Competition Among Platforms - Gal-Or, Esther; Gal-Or, Ronen; Penmetsa, Nabita (Information Systems Research, 2018)
We study the effect of user privacy concerns on competition between online advertising platforms. Online platforms attract advertisers by offering capabilities to reach audiences likely to be receptive to their ads in a timely and accurate manner. However, the collection and processing of user information required for targeting of ads may lead to privacy concerns. We model the competition between two platforms as a two-stage game where platforms announce their targeting capabilities in the first stage and advertising fees in the second stage. The presence of heterogeneity in the user and the advertiser populations with respect to their preferences for targeting leads to differentiation between platforms. While one platform offers the minimum level of targeting feasible, the other platform offers a strictly higher level of targeting. The extent of differentiation in targeting levels depends on the intensity of competition between the platforms on the user side. When competition on the user side is relatively low, the extent of differentiation is higher. Such competition for users may decline, when users are less concerned about loss of privacy or when they choose to double home. Higher targeting differentiation allows platforms to charge higher advertising fees and earn higher profits. We also consider the case where platforms can reduce the privacy concerns of users by offering them greater control over their personal information. We demonstrate that awarding user control leads to reduced targeting differentiation between platforms and lower advertising fees. Last, we derive the equilibrium targeting levels for platforms that use a subscription-based business model instead of an advertising-based business model. The online appendix is available at https://doi.org/10.1287/isre.2017.0730 .